Evaluation of exchange-rate, capital market, and dollarization regimes in the presence of sudden stops - Razin, Asaf 1941-; Rubinstein, Yona 1962- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 2005)
The literature has not being able to identify clear-cut real effects of exchange-rate regimes on output growth. Similarly, no definitive view emerges from the literature in regard to the effects of open capital markets on macroeconomic performance. The paper attributes the failure of the literature to fundamental flaws, consisting of ignoring non-linearities in the effects of exchange rate and capital-market liberalization regimes, on the macroeconomic performance. The paper develops a methodology consisting of accounting for the "crisis-prone state of the economy", summarized by a projected probability of crisis, due to sudden stops in international capital inflows. We apply the new methodology to a cross-country panel of 100 low and middle-income countries. Findings indicate that the effects of exchange rate regimes, and liberalization regimes, on macroeconomic performance go through two distinct channels: a direct channel via the real side of the economy, and an indirect channel via the financial side, which influences the probability of sudden stops. We also analyze how the projected probability of sudden stops affects the level of dollarization, and provide estimates for the effect of dollarization on growth.